Ultrasonographic examination of liver gall bladder in cows - Canpolat, Ibrahim; Han, M. Cengiz; Köm, Mustafa; Dinç, Mehmet (Scientific and Technical Research Council of Turkey, 1996)
Ultrasonografic examination was conducted in healthy adult Holstein cows to reveal the morphological structure, volume and localization of the liver and gall bladder. The localization and diameter of Vena cava and Vena porta were also determined. The ulstrasonografic examination was performed from 7 to 12 intercostal space on the right side of the abdomen. The mesurements of the gall bladder, liver, V. Cava, V. porta were determined by obtaining their image. The findings obtained in this study are expected to be use in the diagnosis of hepatic diseases in cattle.
Si?irlarda Karaci?er ve Safra Kesesinin Ultrasonografisi
Keywords: Cow; Liver and gall bladder; Ultrasonography